Action research methods : plain and simple - Klein, Sheri (Palgrave Macmillan, 2012)
Among the plethora of action research books on the market, there is no one text exclusively devoted to understanding how to acquire and interpret research data. Action Research Methods provides a balanced overview of the quantitative and qualitative methodologies and methods for conducting action research within a variety of educational environments and community-based settings. The text provides balanced coverage of the historical and theoretical foundations for action research while addressing practical and ethical considerations in conducting action research. Key terms and end-of-chapter activities are included to reinforce concepts and engage teachers and researchers in critical reflection.